From conviction to heroism - Pletenac, Tomislav (Traditiones (Ljubljana), 2014)
In 2001, Ante Gotovina, one of the Croatian generals in the Balkan wars of the 1990s, was prosecuted by the ICTY for war crimes committed during the last operation by the Croatian Army, Operation Storm. During his flee, imprisonment and later release we can trace different shifts and splits in Croatian society and popular culture that are closely linked with sovereignty and national identity.
Keywords: Gotovina, Ante, 1955-; sociology; sociologija kulture; national identity; nationalism; nacionalizem; Croatia; vojaška zgodovina; narodna identiteta; osebnosti; popularna kultura; Hrvaška